Effect of integrated financial reporting on firm value with the role of adjusting corporate governance in companies listed on the Iraqi stock exchange - Atatfee, Thaeer Abdulsahib Oglah; Malekian, Esfandiar; Maleki, Bahram Mohseni (Edelweiss Applied Science and Technology, 2024)
The issue of conflict of interests between shareholders and managers and the mechanism of corporate governance as a solution to reduce agency costs associated with it is one of the important issues that has attracted the attention of many researchers and experts due to its effect on the performance of companies. The purpose of this research is the effect of integrated financial reporting on company value with the role of adjusting corporate governance in companies listed on the Iraqi Stock Exchange. The current research is applied in terms of purpose and descriptive and correlational in nature. The time domain of the research covers a period of years, from the beginning of 2016 to the end of 2022. The studied sample included 10 companies that were selected by systematic elimination method. The results of the test of research hypotheses indicated that corporate governance does not have a modifying role in the effect of integrated financial reporting on the value of the company. It seems that in the Iraqi capital market, integrated financial reporting tools cannot help the shareholders in evaluating the company’s value, and other factors affecting the stock price (company’s value) are considered by the shareholders.